Textual Analysis of the Jakarta Post Online Representation of Presidential Candidates in Indonesia - Prayudi Prayudi; Retno Hendariningrum (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2016)
General Election 2014 in Indonesia principally was a gate to more democratic Indonesia. People were given rights to directly vote their preferred legislative representatives and president and vice president for the next five-year period. New political learning process was introduced as all presidential candidates must show their capabilities in all aspects to attract constituents. The role of mass media became important as each candidate worked hard to gain sympathy from people. This paper examines how Indonesian online news media critically reported the presidential candidates. Further, this paper analysed how the issue were represented in the online media and why it was represented in such ways.